Utilization of paramagnetic microparticles for automated isolation of free circulating mRNA as a new tool in prostate cancer diagnostics. Issue 2 (14th September 2013) - Fojtu, Michaela; Gumulec, Jaromir; Balvan, Jan; Raudenska, Martina; Sztalmachova, Marketa; Polanska, Hana; Smerkova, Kristyna; Adam, Vojtech; Kizek, Rene; Masarik, Michal; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> Determination of serum mRNA gained a lot of attention in recent years, particularly from the perspective of disease markers. Streptavidin‐modified paramagnetic particles (SMPs) seem an interesting technique, mainly due to possible automated isolation and high efficiency. The aim of this study was to optimize serum isolation protocol to reduce the consumption of chemicals and sample volume. The following factors were optimized: amounts of (i) paramagnetic particles, (ii) oligo(dT)20 probe, (iii) serum, and (iv) the binding sequence (SMPs, oligo(dT)20, serum vs. oligo(dT)20, serum and SMPs). RNA content was measured, and the expression of metallothionein‐2A as possible prostate cancer marker was analyzed to demonstrate measurable RNA content with ability for RT‐PCR detection. Isolation is possible on serum volume range (10–200 μL) without altering of efficiency or purity. Amount of SMPs can be reduced up to 5 μL, with optimal results within 10–30 μL SMPs. Volume of oligo(dT)20 does not affect efficiency, when used within 0.1–0.4 μL. This optimized protocol was also modified to fit needs of automated one‐step single‐tube analysis with identical efficiency compared to conventional setup. One‐step analysis protocol is considered a promising simplification, making RNA isolation suitable for automatable process.